Vulnerability to omega-3 deprivation in a mouse model of NMDA receptor hypofunction - Rehnuma Islam (Nature Portfolio, 2017)
Glutamate neurotransmission: A weakness for omega-3 Depletion of omega-3 fatty acids in a mouse model of schizophrenia with altered glutamate transmission has a lethal effect in males. Previous studies have suggested that omega-3 supplements may improve the symptoms of schizophrenia. Amy Ramsey and colleagues at the University of Toronto, Canada, show in an established genetic mouse model of the disease that omega-3 dietary supplementation increased brain omega-3 levels, but did not have any beneficial effects on features that mirror symptoms of patients with schizophrenia such as increased locomotor activity or reduced social behavior. Interestingly, omega-3 dietary depletion worsened the cognitive performance and drastically increased the mortality rate of male mutant mice. The mechanisms responsible for these effects remain to be determined, but the findings highlight a potentially serious vulnerability of patients to dietary omega-3 deficits.